Efficacy and safety of tocilizumab with inhibition of interleukin-6 in adult-onset Still's disease: A meta-analysis. Issue 5 (3rd September 2018) - Ma, Yubo; Wu, Meng; Zhang, Xu; Xia, Qing; Yang, Jiajia; Xu, Shengqian; Pan, Faming
Abstract: Objectives: Tocilizumab (TCZ) is the only available biologics inhibiting interleukin-6 presently, and emerging evidences have figured that elevated serum level of interleukin-6 is a crucial link of the pathogenesis of adult-onset Still's disease (AOSD). However, evidence about the efficacy and safety of TCZ in AOSD with strong power is still scarce. Thus, this meta-analysis was conducted to synthetically assess the efficacy and safety of TCZ on AOSD. Methods: PubMed, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure, and Chinese Biological Medical Literature database were comprehensively searched up to 31 July 2017 for the pertinent studies. The pooled remission rates were synthesized by fixed effect model or randomized effects model, depended on heterogeneity. Results: Ten original studies contained 147 individuals were included in our analysis. The overall partial and complete remission rates were 85.38 (95% CI: 69.32–96.88%) and 77.91% (95% CI: 57.91–90.04%), respectively, and the remission rate of refractory patients was 87.92% (95% CI: 56.53–100.00%). Conclusion: The use of TCZ could significantly reduce the need of corticosteroids for AOSD patients. Impressive improvements were attained in both clinical and laboratory parameters. Compared with conventional therapy, TCZ treatment was safety. In conclusion, TCZ was effective and well tolerated for the treatment of AOSD.